PERANAN PRODI BIMBINGAN DAN PENYULUHAN ISLAM DALAM PEMBINAAN KARAKTER MAHASISWA FAKULTAS DAKWAH DAN KOMUNIKASI UIN ALAUDDIN MAKASSAR - Rahmatiah, Rahmatiah; Abbas, Nurlaelah; Islahul Amal, (Jurnal Dakwah Tabligh, 2024)
This study aims to determine the efforts of the study program in developing the character of students of the Islamic Guidance and Counseling Study Program FDK UINAM, as well as the opportunities and challenges of the Study Program in developing the character of students of the Islamic Guidance and Counseling Study Program FDK UINAM. This type of research is descriptive qualitative research using the approach of Islamic Guidance and Psychology. The location of this research is at the Faculty of Da'wah and Communication UIN Alauddin Makassar. The primary data sources in this study are; Sitti Trinurmi the former head of the Islamic Guidance and Counseling Study Program and the additional informant Muh. Ilham is the former head of BPI Study Program, Asni Djamerang, and Muh. Nurlatief as a PA lecturer as well as several Islamic Guidance and Counseling students. Secondary data sources are books, journals, and other documents related to this research and popular writings, the results of research and other publications, and information from the internet relevant to the problem under study. Data collection methods are obtained through observation, interviews, and documentation. Data analysis techniques use data reduction, data presentation, and conclusions. The results of this study show that; First, the efforts made by the Study Program in developing the character of Islamic Guidance and Counseling students, Faculty of Da'wah and Communication UIN Alauddin Makassar are preparing competent lecturers, preparing a representative curriculum by following market developments and needs, exemplary lecturers, preparing Semester Learning Plans (RPS), and the last is to carry out trainings related to character development. Second, the factors that become opportunities in developing the character of students of the Islamic Guidance and Counseling Study Program are many lessons about developing and fostering student character, students obey and obediently hear directions from lecturers, the many experiences that have been passed in fostering student character because the BPI Study Program is the longest Study Program at the Faculty of Da'wah and Communication, then environmental factors also greatly affect student behavior, And the da'wah method becomes a positive supply for students. The challenge is that there are still lecturers who lack discipline with rules, the lack of functioning of some Academic Advisor (PA) lecturers, the laziness factor of students is also a challenge in developing this character, and the last is that there are many students who choose BPI Study Program as a choice.